Reconstructing political economy the great divide in economic thought - Tabb, William K. (London Routledge, 1999)
This volume offers an original perspective on the questions the great economists have asked and looks at their significance for todays world. Written in a provocative and accessible style, it examines how the diverse traditions of political economy have conceptualised economic issues, events and theory. Going beyond the orthodoxies of mainstream economics it shows the relevance of political economy to the debates on the economic meaning of our times.
Includes bibliographical references (p. [250]-280) and index.
Keywords: Economics